Pol-CCES based modulation recognition method under impulsive noise - Jiang’an DAI; Shengyang LUAN; Minglong ZHAO; Zhaojun ZHANG; Tianshuang QIU (Tongxin xuebao)
To realize signal classification in impulsive noise environment， a modulation recognition scheme based on polished cyclic correntropy spectrum and shallow residual network was proposed.The proposed scheme not only has low computational complexity but also shows robustness to impulsive noise.Simulation results demonstrate the proposed solution’s superior performance under impulsive noise， even when the generalized signal-to-noise ratio is very low.